Nanotechnology and the internet of nanothings benefits and risks - Jovanović Popović, Dejana (Sociološki pregled, 2023)
Nanotechnology provides state-of-the-art solutions to a number of applications that have a significant impact on almost every aspect of our community, including medicine, smart cities, army, agriculture, and industry. The intertwining of nanoscale devices with the existing communication networks through the Internet defines a new networking paradigm referred to as the Internet of nanothings, which includes a large number of nanosensors providing more precise and more detailed information on a person’s health, the environment or a particular structure in real time. This paper analyses possibilities for the use of nanotechnologies and the Internet of nanothings, as well as their different applications in smart cities. Finally, this paper presents a discussion on the risks, challenges, and security issues that these two revolutionary techniques may bring to mankind.